1977
DOI: 10.1007/bf00684532
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibrillary accumulation in the zebra (Equus burchelli)

Abstract: Two young zebra siblings from consecutive pregnancies suffered from neurological disease, characterized by ventral deviation of the neck and tetraparesis which progressed to tetraplegia within a few weeks. On histological examination widespread neuronal degeneration was observed in the ventral horns of the spinal cord and in the lower brain stem. Ultrastructurally the neuronal degeneration was characterized by accumulation of neurofibrillary material resembling neurofilaments. The findings are compared to othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Particularly striking examples h~ve been reported in different types of motor neuron diseases, including familial ALS (Hughes and Jerrome 1970;Takahashi et al 1972;Hirano et al 1984b), sporadic ALS (Carpenter 1968;Schochet et al 1969;Hirano et al 1984a), and infantile spinal muscular atrophy (Byers and Banker 1961;Chou and Fakadej 1971;Wiley et al 1987), as well as in spontaneous motor neuron disease in various animal species including dog (Delahunta and Shively 1974;Cork et al 1982), zebra (Higgins et al 1977), rabbit (Shields and Vandevelde 1978), cat (Vandevelde et al 1976) and pig (Higgins et al 1983). The present results, in conjunction with similar findings using transgenic technology of force accumulation of human NF-H in mouse motor neurons (Cote et al 1993), provide an unambiguous demonstration that primary alterations in neurofilament economy can 1) lead to structural changes of the type seen in these neurodegenerative disorders and 2) ultimately lead to axonal breakdown and loss.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Particularly striking examples h~ve been reported in different types of motor neuron diseases, including familial ALS (Hughes and Jerrome 1970;Takahashi et al 1972;Hirano et al 1984b), sporadic ALS (Carpenter 1968;Schochet et al 1969;Hirano et al 1984a), and infantile spinal muscular atrophy (Byers and Banker 1961;Chou and Fakadej 1971;Wiley et al 1987), as well as in spontaneous motor neuron disease in various animal species including dog (Delahunta and Shively 1974;Cork et al 1982), zebra (Higgins et al 1977), rabbit (Shields and Vandevelde 1978), cat (Vandevelde et al 1976) and pig (Higgins et al 1983). The present results, in conjunction with similar findings using transgenic technology of force accumulation of human NF-H in mouse motor neurons (Cote et al 1993), provide an unambiguous demonstration that primary alterations in neurofilament economy can 1) lead to structural changes of the type seen in these neurodegenerative disorders and 2) ultimately lead to axonal breakdown and loss.…”
Section: Discussionmentioning
confidence: 95%
“…Remarkable neurofilament accumulation in the anterior horn a-motor neurons has been found in all such cases (Delahunta and Shively 1974;Vandevelde et al 1976;Higgins et al 1977;Shields and Vandevelde 1978; Cork et al 1982;Higgins et al 1983). These studies have demonstrated that aberrant neurofilament accumulation is a common intermwiate in both early-and late-onset motor neuron disease.…”
Section: Introductionmentioning
confidence: 96%
“…1C) Motor neuron disease, with symptoms resembling infan tile spinal muscular atrophy, has also been described in a number o f animal species. Remarkable neurofilament accu mulation in the anterior horn a-m otor neurons has been found in all such cases (D elahunta and Shively, 1974;Vandevelde et al, 1976;H iggins et al, 1977Shields and V andevelde, 1978;C ork et al, 1982). T hese studies have collectively fueled the speculation that neurofilam ent accu m ulation may represent a com m on initial pathology o f the m otor neuron disease process.…”
Section: Introductionmentioning
confidence: 97%
“…In ALS, there is preferential loss of the large, neurofilament-rich motor axons, although degeneration of large, neurofilament-rich sensory axons is also seen at a lower frequency [ 131. Moreover, immunocytochemistry and electron microscopic examination have clearly shown that accumulation and abnormal assembly of neurofilaments in motor neuron cell bodies and s o n s are common, conspicuous findings in many patients with sporadic [14, 151, cats [16], pigs [17], zebras [18], and rabbits [19].…”
mentioning
confidence: 99%